2012
DOI: 10.1152/ajpcell.00103.2011
|View full text |Cite
|
Sign up to set email alerts
|

H-Ras isoform modulates extracellular matrix synthesis, proliferation, and migration in fibroblasts

Abstract: Ras GTPases are ubiquitous plasma membrane transducers of extracellular stimuli. In addition to their role as oncogenes, Ras GTPases are key regulators of cell function. Each of the Ras isoforms exhibits specific modulatory activity on different cellular pathways. This has prompted researchers to determine the pathophysiological roles of each isoform. There is a proven relationship between the signaling pathways of transforming growth factor-β1 (TGF-β1) and Ras GTPases. To assess the individual role of H-Ras o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 75 publications
(66 reference statements)
3
26
0
2
Order By: Relevance
“…Activation of Ras signaling pathway occurs after early UUO [22, 23], demonstrating a contribution of Ras downstream effectors to renal injury with a main involvement of ERK1/2 in apoptotic events and Akt in proliferative and fibrotic response [23]. There are several Ras isoforms (H-, N- and K-Ras) with different functional properties in fibrotic processes and in fibroblast biology [2426]. Thus, we have observed that H-Ras knock-out (KO) mice show lower fibrosis after UUO [27], whereas in embryonic fibroblasts obtained from H-Ras or N-Ras KO mice, fibronectin and collagen synthesis were higher and proliferation and migration were lower than in wild type fibroblasts [24, 25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of Ras signaling pathway occurs after early UUO [22, 23], demonstrating a contribution of Ras downstream effectors to renal injury with a main involvement of ERK1/2 in apoptotic events and Akt in proliferative and fibrotic response [23]. There are several Ras isoforms (H-, N- and K-Ras) with different functional properties in fibrotic processes and in fibroblast biology [2426]. Thus, we have observed that H-Ras knock-out (KO) mice show lower fibrosis after UUO [27], whereas in embryonic fibroblasts obtained from H-Ras or N-Ras KO mice, fibronectin and collagen synthesis were higher and proliferation and migration were lower than in wild type fibroblasts [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…There are several Ras isoforms (H-, N- and K-Ras) with different functional properties in fibrotic processes and in fibroblast biology [2426]. Thus, we have observed that H-Ras knock-out (KO) mice show lower fibrosis after UUO [27], whereas in embryonic fibroblasts obtained from H-Ras or N-Ras KO mice, fibronectin and collagen synthesis were higher and proliferation and migration were lower than in wild type fibroblasts [24, 25]. Moreover, K-Ras knock-down decreases stimulated proliferation in renal fibroblasts [28] and inhibits fibrosis in a rat experimental model [29].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies highlight the importance of Ha-Ras isoform in the development of fibrosis [4,16,17]. Therefore, we have evaluated the effect of CAA, which selectively blocks Ha-Ras farnesylation [19], on renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…There are three closely related major isoforms of Ras proteins: Harvey (Ha)-, Kirsten (Ki)-, and neural (N)-Ras, which are expressed in mammalian cells and have different biological effects [9,[12][13][14], namely in fibroblasts biology and fibrotic processes [6,[15][16][17]. It has been reported that depletion of Ha-Ras isoform in cultured fibroblasts obtained from Ha-Ras knock-out (KO) mice up-regulates extracellular matrix proteins (ECM) synthesis and mediates proliferation and migration by modulating PI3K/Akt and MEK/ERK activation [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation